Does attention speed up processing? Decreases and increases of processing rates in visual prior entry. - Tünnermann, Jan; Petersen, Anders; Scharlau, Ingrid (Journal of Vision)
Selective visual attention improves performance in many tasks. Among others, it leads to 'prior entry'—earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen’s Theory of Visual Attention, which we use to overcome the limitations of earlier prior-entry assessment with temporal order judgments (TOJs) that only allow relative statements regarding the processing speed of attended and unattended stimuli. Prevalent models of prior entry in TOJs either indirectly predict a pure acceleration or cannot model the difference between acceleration and deceleration. In a paradigm that combines a letter-identification task with TOJs, we show that indeed acceleration of the attended and deceler
Keywords: unattended stimuli; attention speed; cognitive processing; Attention; Humans; Judgment; Mental Recall; Visual Perception; Stimulus Parameters; Visual Perception; Visual Attention; Cognitive Processes; Velocity

Fachsensible Hochschuldidaktik - Scharlau, Ingrid (Teaching is touching the future: Academic teaching within and across disciplines)

Nur Zahlen und Zeichen? Zum Nutzen des Schreibens in der Hochschuldidaktik der Mathematik - Scharlau, Ingrid; Heß, Christiane; Schnieder, Jörn (Neues Handbuch Hochschullehre. 70. Ergänzungslieferung)

Reflection on the Leitmotif "Wrapped in Code" - Scharlau, Ingrid

Real-time Business Process Intelligence. Comparison of different architectural approaches using the example of the order-to-cash process. - Korotina, Anastasiia; Müller, Oliver; Debortoli, Stefan (International Conference on Wirtschaftsinformatik)
Business operations are becoming more and more integrated with the real-time intelligence. Core business activities are being carried out through OLTP systems that provide limited monitoring capabilities of the running process instances. The article shows how to turn the gap between the classic transactional system and the process-centric approach into an organization that provides more accurate and faster decisions on the strategic and operational management levels. This study aims at determination of what kind of information can be retrieved during the process execution and it tries to identify the need for the real-time process intelligence on the example of the order-to-cash process. Furthermore, we compare two architectural approaches of the real-time process intelligence monitoring system. The proposed frameworks retrieve process data from the ERP system in order to record crucial performance indicators on a real-time basis with the use of the in-memory technology.

Multi-Objective Storage Operating Strategy for Industrial Microgrids - Vogt, Thorsten; Fröhleke, Norbert; Böcker, Joachim; Kempen, Stefan (German-Korean Symposium on Power Electronics)

Mehrziel-Speicherbetriebsstrategie für industrielle Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S.

Wortschatzsammler. Evidenzbasierte Strategietherapie lexikalischer Störungen im Kindesalter - Ulrich, Tanja; Motsch, H.J; Marks, D.K

Ein ausbildungsbezogenes Berufsfähigkeitsprofil für angehende Lehrkräfte im Bereich allgemeiner pädagogischer Kompetenz – ein Werkstattbericht - Seifert, Andreas; Israel, Georg; Bentler, Annette; Berning, Hanna; Bredt, Claudia; Buhl, Heike M.; Düsing, Elke; Eilerts, Katja; Günnewig, Kathrin; Trattwal, Hermann; Watson, Christina (Lehrerbildung auf dem Prüfstand)

Inwiefern sollten überfachliche Kompetenzen im Lehramtsstudium stärker gefördert werden? Eine interviewbasierte Studie - Bohndick, Carla; Kohlmeyer, Susanne; Buhl, Heike M. (Lehrerbildung auf dem Prüfstand)

Transparenz im Schriftspracherwerb durch Family Literacy am Beispiel von “LIFE – Lesen in Familie erleben“ - Wiescholek, Sabrina; Hilkenmeier, Johanna; Buhl, Heike M. (Schulpädagogik heute)

Rezension zu: Nicola Kaminski; Volker Mergenthaler: Zuschauer im Eckfenster 1821/22 oder Selbstreflexion der Journalliteratur im Journal(text). Mit einem Faksimile des Zuschauers vom April/Mai 1822 - Öhlschläger, Claudia (Das achtzehnte Jahrhundert 40.2, 2016)

Gibbs measures on permutations over one-dimensional discrete point sets - Richthammer, Thomas; Biskup, Marek (Communications in Mathematical Physics)
We consider Gibbs distributions on permutations of a locally finite infinite set X⊂R, where a permutation σ of X is assigned (formal) energy ∑x∈XV(σ(x)−x). This is motivated by Feynman’s path representation of the quantum Bose gas; the choice X:=Z and V(x):=αx2 is of principal interest. Under suitable regularity conditions on the set X and the potential V, we establish existence and a full classification of the infinite-volume Gibbs measures for this problem, including a result on the number of infinite cycles of typical permutations. Unlike earlier results, our conclusions are not limited to small densities and/or high temperatures.

The rate of convergence to stationarity for M/G/1 models with admission controls via coupling - Kolb, Martin; Stadje, Wolfgang; Wübker, Achim (Stochastic Models)
We study the workload processes of two M/G/1 queueing systems with restricted capacity: in Model 1 any service requirement that would exceed a certain capacity threshold is truncated; in Model 2 new arrivals do not enter the system if they have to wait more than a fixed threshold time in line. For Model 1 we obtain several results concerning the rate of convergence to equilibrium. In particular, we derive uniform bounds for geometric ergodicity with respect to certain subclasses. For Model 2 geometric ergodicity follows from the finiteness of the moment-generating function of the service time distribution. We derive bounds for the convergence rates in special cases. The proofs use the coupling method.

Local asymptotics for the area of random walk excursions - Kolb, Martin; Denisov, Denis; Wachtel, Vitali (Journal of the London Mathematical Society)
We prove a local limit theorem for the area of the positive excursion of random walks with zero mean and finite variance. Our main result complements previous work of Caravenna and Chaumont; Sohier, as well as Kim and Pittel.

Serum sclerostin and DKK1 in relation to exercise against bone loss in experimental bed rest - Belavý, Daniel L.; Baecker, Natalie; Armbrecht, Gabriele; Beller, Gisela; Bühlmeier, Judith; Frings-Meuthen, Petra; Rittweger, Jörn; Roth, Heinz J.; Heer, Martina; Felsenberg, Dieter (Journal of Bone and Mineral Metabolism)
Keywords: Endocrinology; Orthopedics and Sports Medicine; General Medicine; Endocrinology; Diabetes and Metabolism

Glucocorticoid activity and metabolism with NaCl-induced low-grade metabolic acidosis and oral alkalization: results of two randomized controlled trials - Bühlmeier, Judith; Remer, Thomas; Frings-Meuthen, Petra; Maser-Gluth, Christiane; Heer, Martina (Endocrine)
Keywords: Endocrinology; Endocrinology; Diabetes and Metabolism

Towards a gendered history of European literary culture: a (not so) wild wish - Schlieper, Hendrik (PhiN 74)

La Querelle du Cid: la naissance de la politique culturelle française au XVIIieme siècle - Steigerwald, Jörn; Schlieper, Hendrik (Œuvres & Critiques XL,1. Coordinateurs du fascicule)

Neues Licht. Daguerre, Talbot und die Veröffentlichung der Fotografie im Jahr 1839. Steffen Siegel (Hg.): - Süwolto, Leonie (Zeitschrift für Germanistik. Neue Folge XXV)